1973
DOI: 10.1139/v73-113
|View full text |Cite
|
Sign up to set email alerts
|

Some Electron Spin Resonance Observations in the Photoreduction of Nitrobenzenes

Abstract: The photoreduction of some nitrobenzenes in various organic solvents was re-investigated by e.s.r. and the rapid scan e.s.r. method. The present study resolved the contradicting e.s.r. assignments of the radical observed in the photoreduction of nitrobenzene in tetrahydrofuran and confirmed the identification of the radical PhN(0)OR. All other radicals observed in various solvents were identified and their formation can he explained by secondary processes in the photoreduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…This kinetic characteristic may be accounted for by an oxidation mechanism involving an adduct formation of the mesomeric form of 5-oxo-5,6-dihydrouracil-6-yl radical 4 with TNM, but not direct electron transfer. Previously, similar adduct formation was shown in the oxidation of 5-hydroxyuracil-6-yl radical ( 3f ) by nitrobenzenes as well as those of α-hydroxyalkyl and α-alkoxyalkyl radicals by several nitrocompounds, including TNM, as characterized by pulse radiolysis and ESR detection of nitroxide-type adduct radicals.…”
Section: Resultssupporting
confidence: 59%
“…This kinetic characteristic may be accounted for by an oxidation mechanism involving an adduct formation of the mesomeric form of 5-oxo-5,6-dihydrouracil-6-yl radical 4 with TNM, but not direct electron transfer. Previously, similar adduct formation was shown in the oxidation of 5-hydroxyuracil-6-yl radical ( 3f ) by nitrobenzenes as well as those of α-hydroxyalkyl and α-alkoxyalkyl radicals by several nitrocompounds, including TNM, as characterized by pulse radiolysis and ESR detection of nitroxide-type adduct radicals.…”
Section: Resultssupporting
confidence: 59%
“…Generation of aryl alkoxy aminoxyls. Generation of aryl alkoxy aminoxyls utilised a flow apparatus 13 which allows simultaneous mixing of three streams approximately 30 ms prior to passage through a quartz aqueous flow flat-cell positioned in the EPR cavity. For HO ؒ generation the three solutions ‡ contained Ti III [1.67 mM, added as titanium() chloride solution], hydrogen peroxide (8.33 mM) and the substrates [e.g.…”
Section: Photolysis Of Caged Atp Caged Mep and Nitrobenzyl Alcoholsmentioning
confidence: 99%
“…However, it was not produced photochemically and is not, strictly speaking, an ArNO•OH radical. Several steady-state EPR studies of the photochemistry of aromatic nitro compounds were reported, but in most of them only the anion radical ArNO•O - or secondary radicals (ArNO•H, ArNO•R, and ArNO•OR) were observed. ,, Only two ArNO•OH radicals have been reported by steady-state EPR studies: 2,3,5,6-(Cl) 4 −PhNO•OH , and 4-CN−PhNO•OH . Several authors have reported EPR spectra which they attributed to PhNO•OH , but were later discovered to be spectra of PhNO•OR radicals …”
Section: Introductionmentioning
confidence: 99%
“…The attribution of TR-EPR spectra reported here was confirmed by ab initio calculations of the hyperfine coupling constants (hcc's). The DFT method of calculations was first validated on EPR spectra of radicals previously described in the literature. , …”
Section: Introductionmentioning
confidence: 99%